A framework for digital transformation towards smart governance: Using big data tools to target SDGs in Ceará, Brazil - Lara Sucupira Furtado; Ticiana Linhares Coelho da Silva; Marianna Gonçalves Fontenele Ferreira; José Antônio Fernandes de Macedo; Jessika Kantnila de Melo Lima Cavalcanti Moreira (Journal of Urban Management, 2023)
Smart Governance is a key pillar of the Smart City movement and an important pathway to achieving Sustainable Development Goals through digital transformation and technologic tools. However, the digital transformation is highly contextual and solutions from the Global North may not be adequate to the reality of developing countries. We present how digital tools and policies, as part of the broader agenda for digital transformation, can touch upon several sustainability goals when focused on benefitting vulnerable citizens. Examples come from observing the process, stakeholders and products developed during the Digital Transformation of Ceará between 2019 and 2022. We build a framework that further links those examples with the SDGs and the Brazilian Letter for Smart Cities, a national set of guidelines towards equitable smart transitions. By setting the framework vis-a-vis a grounded experience, we seek to present seven components which can be adapted to other contexts as drivers of a Smart and Sustainable Governance. We argue that, by applying those elements to build digital tools that help governance, it is possible to create solutions that are inherently tied to SDGs.
Keywords: 710; Big Data; Brazilian Letter; Digital Transformation; E-Government; SDG 16; Smart City